Psikososyal beceri eğitiminin şizofreni tanısı olan bireylerin yaşam kalitesi üzerine etkisi : meta-analiz çalışması - Öngün, Esen (My University, 2022)
Amaç: Bu çalışmada psikososyal beceri eğitiminin (PSBE) şizofrenili bireylerde yaşam kalitesi üzerine etkisini inceleyen çalışmaları meta-analiz yöntemi ile sentezlemek amaçlandı. Bu çalışmanın amaç ve metodolojisi PROSPERO veri tabanına kayıt edildi (CRD42021235868). Gereç ve Yöntem: 2010-2021 yılları arasında yayınlanmış makalelere The Cochrane Central Register of Controlled Trials (CENTRAL), EBSCOHOST, CINAHL, Pubmed, ScienceDirect, Web of Science, Marmara Üniversitesi Kütüphane Kataloğu ve abone olunan veri tabanları, YÖK Tez Tarama ve ULAKBİM veri tabanları kullanılarak erişildi. Bulgular: PSBE’nin şizofrenili bireylerin yaşam kalitesi toplam puanı üzerinde orta düzeyde (SMD: 0,67; p<0,01), ruhsal boyut üzerinde orta düzeyde (SMD: 0,53; p<0,05), fiziksel boyut üzerinde düşük düzeyde (SMD: 0,38; p<0,05) anlamlı bir etkisi olduğu görüldü. Sonuç: Sonuç olarak psikososyal beceri eğitiminin şizofrenili bireylerde yaşam kalitesini iyileştirmek için kullanılabilecek etkili bir girişim olduğu söylenebilir.

Objective: The aim of this study was to synthesize the studies examining the effects of psychosocial skills training (PST) on the quality of life of people with schizophrenia using a meta-analysis. It is anticipated that this study will provide evidence of the effect of psychosocial skills training on quality of life. The purpose and methodology of this study were recorded in the database PROSPERO (CRD42021235868). Material and Methods: Articles published between 2010-2021 were accessed using databases the Cochrane Central Register of Controlled Trials (CENTRAL), EBSCOHOST, CINAHL, PubMed, ScienceDirect, Web of Science, The Library Catalogue of Marmara University and the subscribed databases, Thesis Center of Council of Higher Education (YÖKTEZ), and Turkish Academic Network and Information Center (ULAKBIM) databases were searched independently by two researchers (EÖ, SÇ). Results: PST was found to have a moderate effect on the overall score of quality of life of individuals with schizophrenia (SMD: 0.67; p<0.01), a moderate effect on the psychological dimension (SMD: 0.53; p<0.05), and a low effect on the physical dimension (SMD: 0.38; p<0.05). Conclusion: Consequently, it can be said that psychosocial skills training is an effective intervention that can be used to improve the quality of life of people with schizophrenia.
Keywords: Beceri Eğitimi; Mental health; Psikiyatri hemşireliği; Psychiatric nursing; Quality of Life; Ruh sağlığı; Skills training; Şizofreni; Yaşam Kalitesi Schizophrenia